2019
DOI: 10.1080/15384047.2019.1683324
|View full text |Cite
|
Sign up to set email alerts
|

Botryllamide G is an ABCG2 inhibitor that improves lapatinib delivery in mouse brain

Abstract: Introduction: Transporters comprising the blood-brain barrier complicate delivery of many therapeutics to the central nervous system. The present study ascertained whether the natural product botryllamide G is viable for in vivo inhibition of ABCG2 using lapatinib as a probe for ABCB1 and ABCG2-mediated efflux from the brain. Methods: Wild-type and Mdr1a/Mdr1b (-/-) mice were treated with botryllamide G and lapatinib ("doublet therapy"), and while a separate cohort of wild-type mice was treated with botryllami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In this work, we have shown that ABCG2 plays an important role in the passage of meloxicam through BBB and its accumulation in the central nervous system. Several studies have demonstrated the limiting role of ABCG2 in the brain penetration of many drugs [49,50] and how transporter inhibition [51,52] or reduced expression due to genetic variants [24] can improve drug therapies related to the central nervous system. We therefore hypothesized that inhibition of ABCG2 could increase brain accumulation of meloxicam, and consequently, improve the potential treatment or prevention of neurodegenerative diseases with this drug.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have shown that ABCG2 plays an important role in the passage of meloxicam through BBB and its accumulation in the central nervous system. Several studies have demonstrated the limiting role of ABCG2 in the brain penetration of many drugs [49,50] and how transporter inhibition [51,52] or reduced expression due to genetic variants [24] can improve drug therapies related to the central nervous system. We therefore hypothesized that inhibition of ABCG2 could increase brain accumulation of meloxicam, and consequently, improve the potential treatment or prevention of neurodegenerative diseases with this drug.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Strope, et al in 2019 investigated a more specific ABCG2 inhibitor, botryllamide G, and found that it could significantly increase brain concentrations of lapatinib. However, ABCB1 would also need to be blocked for a complete efflux transporter inhibition 112 . In addition, off-target effects of Pgp inhibition are a significant pitfall since ABCB1 and ABCG2 are expressed in the gut, liver, and kidney.…”
Section: Blood-brain Barrier Modulationmentioning
confidence: 99%
“…Recently, ABCG2 has received increasing attention due to its mutable pharmacological binding sites (10). Evidence suggested that the upregulation of the ABCG2 gene may be…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ABCG2 has received increasing attention due to its mutable pharmacological binding sites ( 10 ). Evidence suggested that the upregulation of the ABCG2 gene may be closely associated with the high recurrence rate and adverse therapeutic response of hematological malignancies ( 11 ).…”
Section: Introductionmentioning
confidence: 99%